Computers and the history of Art Volume 1 - Harrison, Dew; Worden, Suzette (Intellect Books, 2004)
This paper concerns the ongoing research undertaken in the field of Digital Art at the Digital Media Research Centre, University of the West of England, Bristol (www.media.uwe.ac.uk/). It remains specific to the working partnership developed over the past three years with the Watershed Media Centre (www.watershed.co.uk) where action research has informed working practice, conseuently determining further research. This symbiotic relationship is particularly fruitful in view of the climate of our current technocratic culture where media centres can be understood as the new art galleries for Digital Art in that theya re becoming the main centres for the production, distribution and showcasing of this new art form. The paper discusses the significance of three projects and their outcomes evidencing the rapid changes occurring in this evolving and dynamic field of study and gives an indepth accout of a fourth project, the online exhibition entitled Net_Working, on show at www.dshed.net/networking. It has opened the way for further research into the curation and practice of Digital Art.